Feasibility, effectiveness, and safety of simultaneous side-by-side deployment of uncovered self-expandable metal stents for malignant hilar biliary obstruction: a retrospective single-center study - Zhang-Hagenlocher, Christine; Kantowski, Marcus; Wehling, Cyrill; Michl, Patrick; Koschny, Ronald; Sauer, Peter (BMC gastroenterology, 2025)
Background: Malignant hilar biliary obstruction is associated with a poor prognosis, making biliary drainage important for improving the quality of life. Endoscopic simultaneous side-by-side deployment of uncovered self-expandable metal stents is a novel approach. However, reliable clinical data on this method are limited. This retrospective, single-center study aimed to evaluate the feasibility, effectiveness, and safety of simultaneous side-by-side deployment of self-expandable metal stents for malignant hilar biliary obstruction. Methods: Data from all patients treated for malignant hilar biliary obstruction at our institution between May 2019 and February 2023 were retrospectively analyzed. The primary endpoints were the technical and clinical success rates, while the secondary endpoints included complications, recurrent biliary obstruction, time to recurrent obstruction, reintervention rate, and mortality. Results: Fifteen patients (mean age, 63 years; 8 men) were treated with simultaneous side-by-side deployment of metal stents for malignant hilar biliary obstruction. The location of the biliary obstruction was classified as Bismuth type III (n = 1) or IV (n = 14). Technical and clinical success rates were both 100%. Three patients underwent side-by-side placement of uncovered self-expandable metal stents using the combined percutaneous endoscopic rendezvous technique. The complication rate was 13.3%, with two patients experiencing recurrent biliary obstruction and cholangitis. The median time to recurrent obstruction was 97.5 days (range: 93–102 days). Both patients required reintervention. Moreover, the 30-day mortality rate was 6.7% (n = 1). Conclusions: Endoscopic simultaneous side-by-side deployment of uncovered self-expandable metal stents for unresectable malignant hilar biliary obstruction is feasible and safe, with high success rates. This technique not only effectively controls symptoms through successful biliary drainage, but can also be a promising option for complex anatomic situations when combined with the percutaneous endoscopic rendezvous technique.
Veröffentlicht: 04. Juni 2025
Gesehen am 11.09.2025